A monograph on the isopod family Aegidae in the Tropical Eastern Pacific I The genus Aega - Brusca, R.C (Allan Hancock Foundation : Institute for Marine and Coastal Studies, University of Southern California, 1983)
Allan Hancock monographs in marine biology ; no. 12